Crisis of democracy: beyond malaise and autocratization - Gaspardo, Murilo [UNESP] (London School of Economics and Political Science, 2024)
Is Brazilian democracy in crisis? What are its causes and explanations? What is the legal-institutional dimension of this crisis? What are the specificities and common patterns of Brazil, as a Latin American and Global South country, in the face of the global context? e answers to these e empirical research questions depend on the definition and adjustments of the theoretical lenses (analytical categories or concepts) through which they will be analysed. In this working paper we develop a distinction between: (1) conflicts, instabilities, problems of quality and structural limits that are inherent to the regular performance of liberal-representative democratic regimes; (2) democratic malaise; (3) autocratization; and (4) crisis of democracy. Based on these distinctions, we present elements for analysing the crisis of democracy based on the relationship between politics and law.
Crise da democracia e dos arranjos jurídico-institucionais
Keywords: Democracy; Crisis; Conceptual distinctions; Law; Politics